Use of Shock Index to Identify Mild Hemorrhage: An Observational Study in Military Blood Donors. Issue 3 (29th April 2019) - Pasquier, Pierre; Duron, Sandrine; Pouget, Thomas; Carbonnel, Anne-Charlotte; Boutonnet, Mathieu; Malgras, Brice; Barbier, Olivier; de Saint Maurice, Guillaume; Sailliol, Anne; Ausset, Sylvain; Martinaud, Christophe
Abstract: Introduction: Hemorrhage is the leading cause of preventable death in combat, although early recognition of hemorrhage is still challenging on the battlefield. Hypothesis/Problem: The objective of this study was to describe the shock index (SI) in a healthy military population, and to measure its variation during a controlled blood loss, simulated by blood donation. Methods: A prospective observational study that enrolled military subjects, volunteers for blood donation, was conducted. Demographic and clinical information, concerning both the patient and the blood collection, were recorded. Baseline vital signs were measured, before and after donation, in a 45° supine position. Statistical analysis was performed after calculation of SI. Results: A total of 483 participants were included in the study. The mean blood donation volume was 473mL (SD = 44mL). The median pre- and post-blood donation SI were significantly different: 0.54 (IQR = 0.48-0.63) and 0.57 (IQR = 0.49-0.66), respectively (P = .002). Changes in pre-/post-donation blood pressure (BP) and heart rate (HR) also reached statistical difference but represented a clinically poor relevance. The multivariate analysis showed no significant associations between SI variations and age, sex, body mass index (BMI), sport activities, blood donation volume, and enteral volume replacement (EVR). Conclusion: In this model of mild hemorrhage, SI exhibited significant variations but failed to reach clinical relevance. Further studies are needed to prove the benefit of SI calculation as a possible parameter for early recognition of hemorrhage in combat casualties at the point of injury. Pasquier P, Duron S, Pouget T, Carbonnel AC, Boutonnet M, Malgras B, Barbier O, de Saint Maurice G, Sailliol A, Ausset S, Martinaud C. Use of shock index to identify mild hemorrhage: an observational study in military blood donors. Prehosp Disaster Med. 2019;34(3):303–307.